Early Signals of Vaccine-driven Perturbation Seen in Pneumococcal Carriage Population Genomic Data. (16th May 2019) - Chaguza, Chrispin; Heinsbroek, Ellen; Gladstone, Rebecca A; Tafatatha, Terence; Alaerts, Maaike; Peno, Chikondi; Cornick, Jennifer E; Musicha, Patrick; Bar-Zeev, Naor; Kamng'ona, Arox; Kadioglu, Aras; McGee, Lesley; et al.
Abstract: Background: Pneumococcal conjugate vaccines (PCVs) have reduced pneumococcal diseases globally. Pneumococcal genomic surveys elucidate PCV effects on population structure but are rarely conducted in low-income settings despite the high disease burden. Methods: We undertook whole-genome sequencing (WGS) of 660 pneumococcal isolates collected through surveys from healthy carriers 2 years from 13-valent PCV (PCV13) introduction and 1 year after rollout in northern Malawi. We investigated changes in population structure, within-lineage serotype dynamics, serotype diversity, and frequency of antibiotic resistance (ABR) and accessory genes. Results: In children <5 years of age, frequency and diversity of vaccine serotypes (VTs) decreased significantly post-PCV, but no significant changes occurred in persons ≥5 years of age. Clearance of VT serotypes was consistent across different genetic backgrounds (lineages). There was an increase of nonvaccine serotypes (NVTs)—namely 7C, 15B/C, and 23A—in children <5 years of age, but 28F increased in both age groups. While carriage rates have been recently shown to remain stable post-PCV due to replacement serotypes, there was no change in diversity of NVTs. Additionally, frequency of intermediate-penicillin-resistant lineages decreased post-PCV. Although frequency of ABR genes remained stable, other accessory genes, especially those associated with mobile genetic element and bacteriocins, showed changes in frequency post-PCV. Conclusions: We demonstrate evidence of significant population restructuring post-PCV driven by decreasing frequency of vaccine serotypes and increasing frequency of few NVTs mainly in children under 5. Continued surveillance with WGS remains crucial to fully understand dynamics of the residual VTs and replacement NVT serotypes post-PCV. Abstract : After 13-valent pneumococcal conjugate vaccine (PCV13) introduction in Malawi, the frequency of carried vaccine serotypes decreased significantly across lineages; there was an increase of serotypes 7C, 15B/C, 23A, and 28F; antibiotic resistance rates remained stable; and certain accessory genes changed in frequency.